Student learning behaviors and intervention practices cited among Midwestern teachers referring bilingual CLD students for special education evaluation - Cabral, Robin Morales (Kansas State University, 2008)
Throughout the last several decades, rises in CLD student populations and teacher accountability have factored in the increased numbers of CLD students being referred for, and placed in, special education. Because traditional evaluation processes do not reliably distinguish student learning problems that result from culturally/linguistic difference from those associated with innate disability, once referred, most CLD students go on to be placed in special education. Since over-referral is a key factor in over-representation, the purpose of this qualitative study was to identify and examine the student and teacher factors associated with referral of bilingual CLD students for special education evaluation. The primary sources of data for this study were school records generated by classroom teachers, and semi-structured interviews with teachers who had referred bilingual CLD students for special education evaluation. Qualitative data garnered from these sources permitted identification and description of CLD student learning behaviors, and teacher interpretations thereof, which factored into referral of these students for special education. Results, obtained through review and analysis of 27 referral records and six teacher interview transcripts indicated that lack of teacher preparation was a significant factor in the teacher's ability to appropriately perceive and respond to CLD student learning behaviors. Most notably, grade-level teachers tended to overrate the CLD student's English language proficiency based upon observations made within the school setting. Once determined to have enough English, the CLD student's language needs were essentially disregarded throughout the pre-referral (intervention) process. Student failure with unaccommodative interventions appeared to reinforce teacher perceptions of prereferral as a confirmatory process rather than the means by which student learning problems could be resolved. These phenomena were compounded by the teacher's expressed deference for psychological test data and preference for special education placement. Teachers form observation-based opinions about CLD student language proficiencies which can derail the instructional and intervention process for CLD students and lead to inappropriate referrals for special education. Further research is needed to determine the reliability of such teacher impressions and methods by which these teachers can better identify and respond to CLD student's language assets and needs.
Keywords: Culturally Linguistically Diverse; Special Education; Referral; Education, Special (0529)